Spatial Zoning Strategy for Socio-Economic Development and Environmental Protection in Cu Chi District, Hochiminh City - Huy Anh, Nguyen; Minh Anh, Nguyen Trinh (VNU Journal of Science: Earth and Environmental Sciences; Vol 36 No 1DO - 10.25073/2588-1094/vnuees.4548, 2020)
Cu Chi, with a natural area of 43,496ha, is a district in the northeast of Hochiminh City, where infrastructure has been built intensively and rapidly in recent years. This development results in not only general socio-economic conditions but also the improvement of local welfare. On the other hand, relentless urban and industrial development in Cu Chi District may potentially pose negative impact on general environmental condition due to reduction of green area and industrial waste discharge to the natural ecology. As a consequence, spatial planning and zoning are necessary to balance socio-economic progress and environmental protection for sustainable development. By analyzing the socio-economic, environment and remote sensing data using GIS technology, the research divides the district into 3 major environment zones, including 13 minor sub-zones. Meanwhile, the result also suggests 04 integrated socio-economic development and environmental protection zones as follows: environmental protection with 2 sub-zones (2,286 ha), environmental friendly development with 6 sub-zones (27,753 ha), strengthened environmental management with 4 sub-zones (8,370 ha) and environmental recovery and rehabilitation with 1 sub-zone (5,087 ha). The authors believe that the spatial zoning is important in providing the basis to develop a strategy for socio-economic development and environmental protection for each sub-zone.